Effect of Consumption Values on Women's Choice Behavior Toward Organic Foods: The Case of Organic Yogurt in Iran. Issue 2 (17th February 2017) - Rahnama, Hassan
Abstract: The purpose of this study is to examine the effects of consumption values (i.e., functional value, social value, emotional value, conditional value, epistemic value, environmental value, and health value) on women's choice behavior toward organic yogurt. Structural equation modeling is used to assess data collected by a questionnaire survey. The results indicate that functional value–quality, functional value–taste, and functional value–price; conditional value; epistemic value; and health value have positive effects on choosing organic yogurt by women, and social value, emotional value, and environmental value have no effects on the subject. Among variables, epistemic value and health value have the highest impact on consumer choice behavior toward organic yogurt. So this study concludes that the main influence factors on choice behavior regarding organic yogurt are epistemic value and health value. In fact, consumers have high knowledge about organic yogurt benefits related to their health.